An Adolescent With a Giant Ovarian Cyst and Hyperandrogenism: Case Report - Julio César Moreno-Alfonso; Sara Hernández Martín; Lidia Ayuso González; Alberto Pérez Martínez (Case Reports in Endocrinology)
Conclusion: In adolescents with large ovarian cysts, in addition to ruling out malignant neoplasms, PCOS should be considered as these may have similar clinical and radiological presentations.